(untitled) - Poliak, Milos (Doprava a spoje, 2011)
Paper deals with the analysis of methodology of effective approach to determine the level of excise duty on mineral oils. The first part focuses on the analysis of the level duty on mineral oils in different EU countries. The second part of paper describes a methodology for effective access to the setting of excise duty on mineral oils. The proposal describes two possible.